Facile Installation of 2‐Reverse Prenyl Functionality into Indoles by a Tandem N‐Alkylation–Aza‐Cope Rearrangement Reaction and Its Application in Synthesis. Issue 2 (20th November 2015) - Chen, Xiaobei; Fan, Huaqiang; Zhang, Shilei; Yu, Chenguang; Wang, Wei
Abstract: An unprecedented tandem N‐alkylation–ionic aza‐Cope (or Claisen) rearrangement–hydrolysis reaction of readily available indolyl bromides with enamines is described. Due to the complicated nature of the two processes, an operationally simple N‐alkylation and subsequent microwave‐irradiated ionic aza‐Cope rearrangement–hydrolysis process has been uncovered. The tandem reaction serves as a powerful approach to the preparation of synthetically and biologically important, but challenging, 2‐reverse quaternary‐centered prenylated indoles with high efficiency. Notably, unusual nonaromatic 3‐methylene‐2, 3‐dihydro‐1 H ‐indole architectures, instead of aromatic indoles, are produced. Furthermore, the aza‐Cope rearrangement reaction proceeds highly regioselectively to give the quaternary‐centered reverse prenyl functionality, which often produces a mixture of two regioisomers by reported methods. The synthetic value of the resulting nonaromatic 3‐methylene‐2, 3‐dihydro‐1 H ‐indole architectures has been demonstrated as versatile building blocks in the efficient synthesis of structurally diverse 2‐reverse prenylated indoles, such as indolines, indole‐fused sultams and lactams, and the natural product bruceolline D. Abstract : Challenging synthesis : An operationally efficient N‐alkylation, followed by microwave‐irradiated ionic aza‐Cope rearrangement–hydrolysis, process is reported (see scheme; Ms=mesyl). The tandem process serves as a powerful approach to the preparation of synthetically and biologically important, but challenging, 2‐reverse quaternary‐centered prenylated indoles with high efficiency.